A Educação Física e as finalidades educacionais do ensino médio : um estudo de caso - Araujo, Geander Franco de (2014)
The research is inserted in the physical education field of discussion, intertwining the studies of educational foundations and socio-anthropological body, and its object, the study case with young people who are attending high school in the space / time of physical education classes. . In order to find possible answers to our questions and reflections drawn from Article 35 of LDBEN 9394/96 we ask: To what extent physical education in high school meets the purposes of Article 35 of LDBEN 9394/96? To define and present the problem of this study, we used a theoretical basis through literature research and literatures with the interconnected theme providing theoretical elements for the contribution of a comprehensive view of the researched object. The universe of research involves the State School Jaime Veríssimo de Campos "Jaiminho" and the regular high school classes of the morning period. Semi-structured interviews were conducted as a physical education teacher in high school and the school with 21 young people who were enrolled from the 1st to 3rd year of high school. Were also effected, observations of physical education lessons through semistructured script advisor. Through this descriptive research, we focus our research on the responses of these students, based on their educational experiences contrasting them with the investigated literature and from proposals / legal and policy documents that come currently being discussed in the higher spheres of Basic Education. Therefore, we propose through the student responses and observations of classes, the theoretical assumptions and the legal documents analyzed to understand the physical education answers the legal guidelines of Article 35 of LDBEN 9.394 / 96. It was found that while physical education try to be a curricular component that promotes a transformative practice as the law perspective, this process is not given is in constitution, signaling a reinterpretation of the current scenario this context. In this sense, we observed that the representations of the students and teacher practice in the school investigated express propositions that instrumentalize for the physically active life responding to the desires of society.